The accompanying adult: authority to give consent in the UK - SEEMA MADHUR LATA LAL, SUSAN PAREKH, CAROL MASON, & GRAHAM ROBERTS (IAPD and Blackwell, 2007)
Children may be accompanied by various people when attending for dental treatment. Before treatment is started, there is a legal requirement that the operator obtain informed consent for the proposed procedure. In the case of minors, the person authorized to give consent (parental responsibility) is usually a parent.